Democracy among the mountaineers : text Pedro Bundok, prints - Bundok, Pedro (Quezon City : New Day Publishers, 1973)
Title taken from cover
When a man is drunk
Keywords: Mountain people -- Addresses, essays, lectures -- Philippines